Is cannabis use associated with an increased risk of onset and persistence of alcohol use disorders? A three-year prospective study among adults in the United States. (1st April 2016) - Weinberger, Andrea H.; Platt, Jonathan; Goodwin, Renee D.
Highlights: Cannabis use was associated with increased incidence of alcohol use disorders. Cannabis use predicted persistence of alcohol use disorder three years later. Relationships remained significant controlling for demographics and comorbidities. Integrating assessment of cannabis use into alcohol treatment may be beneficial. Abstract: Background: The relationship between cannabis use and alcohol use disorders (AUDs) over time remains unclear. The current study used longitudinal data from adults in the United States (U.S.) to investigate the association between cannabis use and risk of onset and persistence of AUDs three years later. Methods: The study used data from respondents who completed both waves of the National Epidemiological Study of Alcohol Use and Related Disorders (NESARC; Wave 1, 2001–2001; Wave 2, 2004–2005) and for whom the age of first cannabis use preceded the age of any AUD. Incident AUDs were examined among respondents with no lifetime AUD diagnosis at Wave 1 ( n = 27, 461). Persistent AUDs were examined among respondents with a lifetime AUD diagnosis at Wave 1 ( n = 2, 121). Results: Among adults with no history of AUD, cannabis use at Wave 1 was associated with increased incidence of an AUD three years later relative to no cannabis use (Odds Ratio (OR) = 5.43; 95% Confidence Interval (CI) = 4.54–6.49). Among adults with a history of AUD, cannabis use at Wave 1 was associated with increased likelihood of AUD persistence three years later relative to no cannabis use (OR = 1.74; 95% CI = 1.56–1.95). These relationships remained significant after controlling for demographics, psychiatric disorders, and other substance use disorders. Conclusions: Cannabis use is associated with increased risk of AUD onset and persistence over the course of three years among U.S. adults. Community-based and clinical programs aimed at preventing or treating problematic alcohol use may benefit from integrating information about cannabis use in order to improve outcomes.